An Energy Eﬃcient MAC Protocol for Linear WSNs. Issue 4 (1st October 2015) - Dai, Guoyong; Miao, Chunyu; Ying, Kezhen; Wang, Kai; Chen, Qingzhang
Abstract : Wireless sensor networks (WSNs) have been employed as an ideal solution in many applications for data gathering in harsh environment. Energy consumption is a key issue in wireless sensor networks since nodes are often battery operated. Medium access control (MAC) protocol plays an important role in energy eﬃciency in wireless sensor networks because nodes' access to the shared medium is coordinated by the MAC layer. An energy efﬁcient MAC protocol is designed for data gathering in linear wireless sensor networks. In order to enhance the performance, when a source node transmits data to the sink, proper relay nodes are selected for forwarding data according to the energy consumption factor and residual energy balance factor. Some simulation experiments are conducted and the results show that, the proposed protocol provides better energy eﬃciency and long lifetime than the existing DMAC protocol.